Influеnce of alkaline earth metal oxides on the properties of fluor- and boron-free enamels - Белый, Яков Иванович; Голеус, Виктор Иванович; Павлова, Екатерина Викторовна; Кисличная, Раиса Ивановна (Technology audit and production reserves, 2013)
These days, plenty of industries widely utilize various kinds of enamelware, which must comply with State Standards, look attractive, be safe and easy-to-use. However, the production of such ware requires the enamel, containing detrimental and unhealthy impurities of fluorine as well as boron. Yet, the compounds with these elements give enamel numerous positive qualities, including fusibility, viscosity of their melt and luster of the glass coating. This article sets forth the results of analyzing the influence of alkaline earth oxides (СаО, МgO and SrO) on the fluorine- and boron-free coating enamel properties. It’s been ascertained, that the mentioned oxides have positive influence on physicochemical enamel properties (i.e. chemical resistance and the temperature coefficient of linear expansion - TCLE), as well as optical characteristics of experimental enamel coatings. The developed fluorine- and boron-free enamels can lower expenses for raw materials, preclude the lixiviation of boric oxide from enamel coatings and reduce industrial environment pollution with toxic substances (e.g. alkaline metaborates and fluorine compounds), which are emitted during the enamel melting process. The new enamels can serve as the basic materials for colored fluorine- and boron-free enamels used for coating everyday household goods.